Perancangan Sistem Rental Mobil untuk Meningkatkan Efisiensi Manajemen Data - Ilham Abdul Aziz; Suryo Nugroho Setyo Aji; Indrawan Ady Saputro (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The application of technology in all areas of life must be increased to support digital transformation, especially in Indonesia. In this research, technology is applied in terms of managing data in car rental services as a means to make the work of rental service providers easier. This research also aims to build a car rental system that focuses on helping car rental service managers to face the digital era that focuses on the use of technology. The data collection method in this research uses literature study as an aspect of understanding for researchers in knowing user needs. By using the prototype method as a system development medium which consists of requirements gathering and analysis stages, identification of system needs and objectives, and design to build the required system.